THE INFLUENCE OF COMPETENCY AND USE OF INFORMATION TECHNOLOGY ON OPERATIONAL EFFICIENCY THROUGH THE QUALITY OF FINANCIAL REPORTS IN KOREM 083/BDJ - Putu Hendra Putra; Diyah Sukanti Cahyaningsih; Gaguk Apriyanto (PT. Jurnal Center Indonesia Publisher, 2025)
The need for accountability in Indonesian government demands transparency and accurate financial reports. This research examines the influence of work competency and the use of information technology (IT) on the quality of financial reports and their impact on the operational efficiency of Korem 083/BDJ. With quantitative descriptive methods and path analysis using SmartPLS and SEM-PLS, this research involved employees in the planning and finance fields. The variables studied include work competency, IT utilization, financial report quality, and operational efficiency. The research results show that IT utilization has a positive impact on operational efficiency, while work competency has a negative impact. However, work and IT competencies contribute positively to the quality of financial reports, which ultimately increases operational efficiency. The quality of financial reports has also been proven to mediate the relationship between work competency, IT utilization and operational efficiency. These findings confirm that increasing operational efficiency is very dependent on the quality of financial reports as well as optimizing information technology and work competencies.